2D Molecular Semiconductors: 2D Single‐Crystalline Molecular Semiconductors with Precise Layer Definition Achieved by Floating‐Coffee‐Ring‐Driven Assembly (Adv. Funct. Mater. 19/2016). (May 2016) - Wang, Qijing; Qian, Jun; Li, Yun; Zhang, Yuhan; He, Daowei; Jiang, Sai; Wang, Yu; Wang, Xinran; Pan, Lijia; Wang, Junzhuan; Wang, Xizhang; Hu, Zheng; et al.
Abstract : On page 3139, Y. Li, X. Wang, Y. Shi, and co‐workers demonstrate a new strategy for the rapid growth of 2D single‐crystalline molecular semiconductors with precise layer definition by a floating‐coffee‐ring‐driven assembly. In particular, using bilayer molecular crystals, the field‐effect transistors yield a maximum carrier mobility of 13.0 cm 2 V −1 s −1 . This strategy helps improve this new class of 2D materials in low‐cost, large‐area, and high‐performance electronics.